Comparative and international criminal justice systems: policing, judiciary, and corrections - Ebbe, Obi N. Ignatius (CRC Press, Taylor & Francis Group, 2013)
The nature of comparative and international criminal justice -- The purpose of comparative and international criminal justice systems / Obi N. Ignatius Ebbe -- Crime : international and comparative / Obi N. Ignatius Ebbe -- Criminal law / Obi N. Ignatius Ebbe -- Criminal justice system in the United States / Mary Clifford -- The criminal justice system of Ireland / Paul Douglas O'Mahony -- The criminal justice system in Israel / Maria R. Haberfeld and Sergio Herzog -- The criminal justice system in Argentina / Obi N. Ignatius Ebbe and Ruben G. Ruiz de Olano -- The criminal justice system of Sierra Leone / Bankole Thompson -- Administration of justice in Poland / Emil W. Plywaczewski -- The criminal justice system and police in Russia : general overview / Yakov Gilinskiy -- Interpol and international police cooperation / Obi N. Ignatius Ebbe -- Policing and public disorder in the United Kingdom / Michael Bullock -- The police system in the people's republic of China / John Zheng Wang -- World courts of justice of the United Nations / Obi N. Ignatius Ebbe -- The judiciary and criminal procedure in Nigeria / Obi N. Ignatius Ebbe -- The Islamic criminal justice system / Obi N. Ignatius Ebbe and Jonathan Odo -- The court system in the people's republic of China with a case study of a criminal trial / Robert Davidson and John Zheng Wang -- United Nations provisions for punishment of offenders vis-à-vis punishment of offenders in history / Obi N. Ignatius Ebbe -- Guided change in Japan : the correctional association prison industrial cooperative (CAPIC) and prison industry / Elmer H. Johnson -- Treatment of offenders in Denmark and Brazil / Zelma W. Henriques -- The unique and comparative features of the criminal justice systems, international law, and the United Nations criminal courts : a synthesis / Obi N. Ignatius Ebbe